Optimalisasi Manejemen Risiko Operasional Bank Syariah melalui Transformasi Digital dalam Menghadapi Peluang dan Tantangan - Firdaus, Violinda Syahgaria (Maliki Interdisciplinary Journal, 2025)
This study aims to examine how digital transformation can be optimized in the management of operational risk in Islamic banks. Digital transformation has become a strategic necessity in the modern era, but it also presents new challenges for the financial sector, including increasingly complex operational risks. These risks include system disruptions, human error, cyberattacks, and the misalignment of digital systems with sharia principles. Using a literature review approach, this article identifies the opportunities offered by digitalization, such as improved efficiency, enhanced data security, and the expansion of financial services. However, challenges such as low digital literacy, infrastructure limitations, and regulatory misalignment remain significant obstacles. The findings indicate that optimizing digital transformation in operational risk management can be achieved through strengthening digital security systems, developing human resource competencies, ensuring sharia compliance in digital innovation, and fostering cross-sector collaboration. With an integrated and sustainable strategy, Islamic banks can maintain operational continuity and enhance their competitiveness in the era of global financial digitalization.